Study on awareness of microbeads pollution from personal care products - Ain Najwa Abd Latif (2020)
Microbeads are synthetic organic polymers that usually found in personal care products such as exfoliating body washes, facial scrub and sunscreen. Due to size of microbeads are smaller than 5 millimetre, they are unable to be filtered by wastewater treatment plant. This can be resulted in microbeads pollution which is harmful to environment and also human health. Thus, by studying the awareness of students in UMK Jeli Campus on microbeads pollution can help in improving awareness among students and also reduce the usage of personal care products which contain microbeads. Therefore, this study aims to analyze the knowledge on microbeads pollution towards their attitudes in choosing personal care products and evaluate students' perceptions on personal care products containing microbeads. The method used in this study is survey by using questionnaire. The stratified random sampling method is used where the students are divided based on their faculty. The percentage of students that have knowledge on microbeads pollution are 65.43 %. The percentage of students that practicing good attitudes in choosing personal care products are 65.51 %. Meanwhile the percentage of students that concerned on microbeads pollution are 75.68 % and the percentage of students that aware on microbeads pollution are 72.96 %. The results showed that students have good knowledge on microbeads pollution and concerned on microbeads pollution. However, their attitudes in reducing the used on microbeads are lower than their awareness on microbeads pollution issues.